2021
DOI: 10.1177/0271678x20978582
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of quantifying hemodynamic delays to improve hemodynamic response, and CVR estimates in CO2 challenge fMRI

Abstract: Elevated carbon dioxide (CO2) in breathing air is widely used as a vasoactive stimulus to assess cerebrovascular functions under hypercapnia (i.e., “stress test” for the brain). Blood-oxygen-level-dependent (BOLD) is a contrast mechanism used in functional magnetic resonance imaging (fMRI). BOLD is used to study CO2-induced cerebrovascular reactivity (CVR), which is defined as the voxel-wise percentage BOLD signal change per mmHg change in the arterial partial pressure of CO2 (PaCO2). Besides the CVR, two addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…For the correction of CO 2 fluctuations on the fMRI signal, the HRF CO 2 can be convolved with end-tidal CO 2 data, and the output regressed out of the BOLD signal (Prokopiou et al, 2019). Use of end-tidal CO 2 measurements can also be useful when the user requires creation of the estimated CO 2 arrival time at each brain region and quantification of the hemodynamic response following elevation of CO 2 (Yao et al, 2021).…”
Section: Functional Mri Of the Brainstem In Relation To Respirationmentioning
confidence: 99%
“…For the correction of CO 2 fluctuations on the fMRI signal, the HRF CO 2 can be convolved with end-tidal CO 2 data, and the output regressed out of the BOLD signal (Prokopiou et al, 2019). Use of end-tidal CO 2 measurements can also be useful when the user requires creation of the estimated CO 2 arrival time at each brain region and quantification of the hemodynamic response following elevation of CO 2 (Yao et al, 2021).…”
Section: Functional Mri Of the Brainstem In Relation To Respirationmentioning
confidence: 99%
“…The CVR, thus, represents the linear relationship of %BOLD and hypercapnic vasoactive stimulation for each voxel. 27,[47][48][49] To estimate the relative change in CBV, we first used the %DBOLD values from the hyperoxia condition (%D BOLD ho ) to estimate the M-value using the hyperoxiacalibrated BOLD model from Chiarelli et al: 50…”
Section: Fmri Data Analysismentioning
confidence: 99%
“…Transfer function analysis can be used to identify phase, gain, and coherence metrics ( Duffin et al, 2015 ). Sinusoidal stimuli may be used ( Blockley et al, 2011 ), and the linear fit between the observed BOLD signal and the arrival-time adjusted P ET CO 2 convolved with the hemodynamic response function ( Yao et al, 2021 ).…”
Section: A New Cvr Metric: Speed Of Responsementioning
confidence: 99%